A Techno Economic Analysis of 2MW On-Grid Solar Power Plant for Tourist City Chavy – Land - Majeed, Asso R.; Kez, Dlzar Al (Sulaimani Journal for Pure and Applied Sciences, 2019)
Iraqi Kurdistan Region has a big potential in solar energy, because of its location and territorial extension. Yet the exploration of this technology not widely accepted in this region due to some reasons including the high installation cost, the lack of experience and technical unknowns. In this paper, a techno-economic analysis has been carried out to resolve some of these unknowns using 2MW solar power system and Chavy land city as a test bed. The system tries to contribute to part of daily energy demand of the place. The well-known computational System Advisor Model (SAM) simulation used to run technical and financial analysis. Simulation results showed that the system contributes significantly to power the area and reduce the load on the national grid. Although initial installation cost shows high prices, within a short period it would not only recover installation costs but also help gain substantial disbursement through the lifetime of the system.
Keywords: Solar photovoltaic system; Global horizontal irradiation; Gridconnected; Load flow